OCP Oracle Certified Professional Java SE 11 Programmer I : study guide : exam 1Z0-815 - Boyarsky, Jeanne; Selikoff, Scott (Newark : John Wiley & Sons, Incorporated, 2020)
The comprehensive study aide for those preparing for the new Oracle Certified Professional Java SE Programmer I Exam 1Z0-815 Used primarily in mobile and desktop application development, Java is a platform-independent, object-oriented programming language. It is the principal language used in Android application development as well as a popular language for client-side cloud applications. Oracle has updated its Java Programmer certification tracks for Oracle Certified Professional.' OCP Oracle Certified Professional Java SE 11 Programmer I Study Guide covers 100% of the exam objectives, ensuring that you are thoroughly prepared for this challenging certification exam. This comprehensive, in-depth study guide helps you develop the functional-programming knowledge required to pass the exam and earn certification. All vital topics are covered, including Java building blocks, operators and loops, String and StringBuilder, Array and ArrayList, and more. Included is access to Sybex's superior online interactive learning environment and test bank'containing self-assessment tests, chapter tests, bonus practice exam questions, electronic flashcards, and a searchable glossary of important terms. This indispensable guide: -Clarifies complex material and strengthens your comprehension and retention of key topics -Covers all exam objectives such as methods and encapsulation, exceptions, inheriting abstract classes and interfaces, and Java 8 Dates and Lambda Expressions -Explains object-oriented design principles and patterns -Helps you master the fundamentals of functional programming -Enables you to create Java solutions applicable to real-world scenarios There are over 9 millions developers using Java around the world, yet hiring managers face challenges filling open positions with qualified candidates. The OCP Oracle Certified Professional Java SE 11 Programmer I Study Guide will help you take the next step in your career.
Front Matter -- Welcome to Java -- Java Building Blocks -- Operators -- Making Decisions -- Core Java APIs -- Lambdas and Functional Interfaces -- Methods and Encapsulation -- Class Design -- Advanced Class Design -- Exceptions -- Modules.
Includes index.
CSE
Karim International
Keywords: Java (Computer program language) -- Examinations -- Study guides; Computer science